A prospective randomized trial of desmopressin in canine mammary carcinoma. (18th June 2020) - Sorenmo, Karin; Durham, Amy C.; Evans, Brolin; Scavello, Heather; Stefanovski, Darko
Abstract: Metastatic disease represents a serious and often fatal development in patients with solid tumours, including women with breast cancer and dogs with mammary tumours. Therefore, preventing and treating metastatic disease has remained a priority in cancer research. Desmopressin, a synthetic derivative of vasopressin, traditionally used to treat patients with bleeding disorders, has been proposed as a potential anti‐metastatic agent due to its effect on haemostasis as well as multiple other anti‐proliferative and anti‐angiogenic mechanisms. The purpose of this study was to retest desmopressin in dogs with mammary carcinomas. A prospective randomized study was performed. Twenty‐four dogs with mammary carcinomas were enrolled; 12 dogs received perioperative desmopressin and 12 received placebo. All dogs underwent standard pre‐surgical staging followed by complete resection of all tumours. Intact dogs were spayed. All tumours were graded and classified according to the published guidelines. Follow‐up was performed every 4 months the first year and every 6 months thereafter. Necropsies were requested on all dogs. There was no difference in time to primary metastasis or survival between desmopressin treated dogs and the placebo arm ( P = .43 and .73, respectively). The distribution of negative prognostic factors, including tumour grade, stage, and high vs low bioscore (refined flexible bioscoring) category between arms was not statistically different, even though more dogs in the placebo arm had grade 3 tumours and high bioscores. Based on the results of this study, perioperative desmopressin does not prevent metastasis in dogs with mammary carcinomas.